Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

If the sum of p terms of an AP is equal to the sum of q terms,then show that the sum of its p+q terms is zero.{plz. answer fast.}

Asked by vrushali 28th February 2013, 11:54 AM
Answered by Expert
Answer:

Sp=Sq

p/2[2a +(p-1)d]=q/2 [2a+(q-1)d]

p[2a +pd - d]=q[2a+qd - d ]

2ap + p2d - pd =2aq + q2d -qd

2ap-2aq +p2d -q2d -pd +qd =0

2a (p-q) +(p+q)(p-q)d -d(p-q)=0

(p-q)[2a + (p+q)d - d ]=0

(p-q)/2[2a + (p+q)d - d ]=0

Hence, the sum of its first (p+q) terms is 0.

Answered by Expert 28th February 2013, 1:12 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!